Patterns of Adherence to COVID-19 Preventive Behaviors and Its Associated Factors: A Cross-sectional Study in Yogyakarta, Indonesia - Septi Kurnia Lestari; Ratri Kusuma Wardani; Eggi Arguni; Jajah Fachiroh; Lutfan Lazuardi; Teguh Haryo Sasongko; Nawi Ng; Fatwa Sari Tetra Dewi (Wolters Kluwer Medknow Publications, 2024)
Introduction: Adherence to COVID-19 preventive behaviors is crucial in controlling the COVID-19 pandemic in Indonesia, but it relies on voluntary participation. Therefore, understanding adherence patterns is vital for designing effective interventions. This study aims to identify groups of adherence patterns and associated factors among adults in Sleman Regency, Yogyakarta, Indonesia. Methods: Cross-sectional secondary analyses were conducted on data from 409 healthy adults who participated in the SurveIllaNce sysTEm to observe seroconverSIon to SARS-CoV-2 in humans study. Patterns of adherence to COVID-19 preventive behaviors, such as face mask wearing, respiratory etiquette, handwashing, physical distancing, not traveling out of the region, avoiding social gatherings, and avoiding going out for a walk, shopping, or meeting others, were identified using latent class analysis (LCA). Factors associated with adherence groups and frailty were examined using multinomial regression analyses integrated with LCA. Results: Three adherence groups were identified: high (65.2%), moderate (13.7%), and low adherence (21.1%). Women (adjusted odds ratio [aOR]: 4.5; 95% confidence interval [CI]: 1.8-10.9) and married individuals (aOR: 3.8; 95% CI: 1.7-8.3) were more likely to belong to the high adherence group, while older adults (aOR: 0.5; 95% CI: 0.22-0.96) and those with COVID-19-like symptoms (aOR: 0.2; 95% CI: 0.03-0.89) had a higher likelihood to be in the low adherence group. Conclusion: Differences in adherence patterns may exist among individuals with varying personal characteristics. Thus, it is imperative to develop tailored health promotion strategies that target specific demographic groups with lower adherence.